A Critical Analysis of the Problems in Communicative English Faced by Learners in Engineering Colleges - Thomas, Joseph (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
A critical study is conducted in a premier Engineering college in Tamil Nadu.This Institution enjoys an excellent status in terms of admissions, extra-curricular activities and placement. Meritorious students with high scores in plus two are admitted every year. The institution takes up a series of steps to improve the communication skills of learners. Despite these efforts, many final year students are unfit to be placed due to low proficiency in the basic skills of English language. Hence the study aims at identifying their problems with communication skills, analyzing the causes and suggesting remedies for improvement. Every class room has a heterogeneous group of students from different educational streams such as- CBSE, matriculation and state board. A majority of students have had their schooling in Tamil medium. Further, they hail from different backgrounds, rural, semirural and urban. Technical English is included in the curriculum only in first and second semesters, where concentration is on teaching grammar items. In the fifth semester, every branch of students is given a three hour training per week in the communication lab. The study reveals that the learners indifference and lack of intrinsic motivation is the prime cause for low proficiency. The evaluation system compels the faculty to complete the syllabus from an examination point of view. This is another handicap which prevents the teachers from imparting the required communication competency within the prescribed hours. It is hoped that this study will create awareness among the language teachers to discover more efficient methods to cope up with the learners need.